The phenomenon of scientific school at higher art education - Dyba, T. (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the essence and peculiarities of the scientific school in the coordinate system of higher art education, also in the field of paradigmatic perspective. Characterized by the identification characteristics of scientific schools in higher arts education and their achievements. Conducted historical digression into the problem of determining the nature, structure and characteristics of the scientific school at different stages of social development. Based on the analysis of modern concepts’ identification of scientific schools described the major trends in reproduction research culture in the scientific community. The article highlights leading scientific schools at art education since the time of independence of Ukraine. It is emphasized that the mechanism of occurrence of a new school is the differentiation of the old school or the integration around a new direction of research. Paradigms of Thomas Kuhn “found” by studying the system’s organization of cognitive group or reputable research samples, which are used as new search models. A crucial role is played by the commonality of aims, scientific-methodological commonality of evaluation criteria and the most importantly is the presence of a leader, the author of the original ideas and methods. A significant role in the development of scientific schools is their influence on art education. Scientific schools in higher arts education provide the reproduction of scientific-pedagogical culture in the next generation of scientists.